Pengaruh Model Pembelajaran Mind Mapping Terhadap Motivasi dan Hasil Belajar Siswa pada Materi Ekosistem - Wahyuni, Nurmala Kiki; Nurlia, Nurlia; Haruna, Moh. Fahri (Universitas Negeri Makassar, 2021)
Abstract. The purpose of this study was to know: 1) the influence of the mind mapping learning model to student's learning motivation in ecosytem material class X at SMA Negeri 1 Bunta, 2) the influence of the mind mapping learning model to student learning outcomes in ecosytem material class X at SMA Negeri 1 Bunta. The research method is a quasi-experiment and uses a pretest - posttest control group design.The population in this study were all students of class X MIPA SMA Negeri 1 Bunta as many as 4 classes, while the sample was class X MIPA 4 as the experimental class and class X MIPA 3 as the control class. The data collection techniques used by learning motivation questionnaire and study result test The results of research indicate: 1) there is influence of the mind mapping method to learning motivation in ecosytem material class X at SMA Negeri 1 Bunta obtained sig. 0.001 <0.05, 2) there is influence of the mind mapping method to learning outcomes in in ecosytem material class X at SMA Negeri 1 Bunta obtained sig. 0.005 <0.05.Keywords: learning outcomes, mind mapping, learning motivation.